2015
DOI: 10.1039/c5dt01254f
|View full text |Cite
|
Sign up to set email alerts
|

A giant magnetocaloric effect with a tunable temperature transition close to room temperature in Na-deficient La0.8Na0.2−xxMnO3manganites

Abstract: A giant magnetocaloric effect induced by sodium-deficiency in a La0.8Na0.2-x□xMnO3 (0.00 ≤ x ≤ 0.15) polycrystalline sample is reported in the present research work. The ability to tune the temperature transition close to room temperature is revealed to be possible by changing the sodium-deficiency content as well. All samples were synthesized using solid-solid reaction. X-ray diffraction and magnetization measurements were performed to investigate their crystallographic structure and magnetocaloric properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Thus, the resulting RCP values are found to be 104.2 and 263.5 J kg À1 under a magnetic eld changes of 2 and 5 T, respectively. The obtained values are comparable with those of several manganite systems with a large MCE, [26][27][28][29][30][31][32] suggesting that our compound may be suitable candidate for magnetic refrigeration. The large MCE in Pr 0.65 -Ca 0.25 Ba 0.1 MnO 3 can be understood by its sharp magnetization change at the FM-PM transition and its high magnetization saturation.…”
Section: (B) Magnetic and Magnetocaloric Effectsupporting
confidence: 78%
“…Thus, the resulting RCP values are found to be 104.2 and 263.5 J kg À1 under a magnetic eld changes of 2 and 5 T, respectively. The obtained values are comparable with those of several manganite systems with a large MCE, [26][27][28][29][30][31][32] suggesting that our compound may be suitable candidate for magnetic refrigeration. The large MCE in Pr 0.65 -Ca 0.25 Ba 0.1 MnO 3 can be understood by its sharp magnetization change at the FM-PM transition and its high magnetization saturation.…”
Section: (B) Magnetic and Magnetocaloric Effectsupporting
confidence: 78%
“…However, Zhang et al [21] observed that Tc decreased with increase in the grain size in the range of 24.4-240 nm. It is known that this variation of Tc is controlled by the electron bandwidth W and the mobility of eg electrons [11,22,23]. In fact, the structure, magnetism, and the magnetocaloric effect are very correlated, primarily by the bandwidth W.…”
Section: Resultsmentioning
confidence: 99%
“…transition temperature as a function of the Mn +4 fraction in La-manganites (data taken from supplemental material of [29] and [31][32][33][34][35][36][37]). [29] and [31][32][33][34][35][36][37]).…”
Section: Figurementioning
confidence: 99%